Utah : with Zion, Bryce Canyon, Arches, Capitol Reef & Canyonlands National Parks - Silver, Maya (Oakland, CA : Avalon Travel, Hachette Book Group, 2024)
"From remote deserts and arid mountain ranges to colorful canyons and world-famous national parks, Moon Utah reveals the best of this adventurous state. With Moon's practical advice and local insight on the best things to do and see, you can experience the best of Utah"--
Welcome to Utah -- Salt Lake City and Northern Utah -- Park City and the Wasatch Back -- Zion and Bryce -- The Escalante area and Capitol Reef -- Moab, Arches, and Canyonlands -- Southeast Utah -- Uinta Mountains and dinosaur country -- Background -- Essentials -- Resources.
"Strategic itineraries - Year-round recreation -Avoid the crowds"--Cover.
Includes index.
Keywords: National parks and reserves -- Utah -- Guidebooks; Utah -- Guidebooks; Zion National Park (Utah) -- Guidebooks; Bryce Canyon National Park (Utah) -- Guidebooks; Arches National Park (Utah) -- Guidebooks; Capitol Reef National Park (Utah) -- Guidebooks; Canyonlands National Park (Utah) -- Guidebooks; Guidebooks